Significant Medical Study Written in Kosovo in the 17th Century Content Analysis of an Anonymous Medicinal Book Written In Kosovo in the 17th Century - Koro , Hüsniye; Millaku , Shkelqim (International Journal of Membrane Science and Technology, 2023)
The aim of this studies is to analyze an anonymous medicinal book on medicinal herbs written in 1610 at the Halved lodge in Rahovec, Kosova. This book was written in Turkish during the Ottoman Empire and it has not been studied before. The author, a Sufi wise, wrote his works in poetic style and in Turkish, Albanian, Arabic and also French. Since this person is a well-known doctor in the region where he lives, it is thought that he treated people throughout his life and wrote this work for new doctors to use in their treatment due to the lack of doctors. The treatment information in the book has been used for many years during and after the author's time. In addition, it is thought that this information, which includes the doses of drugs and medicinal herbs used in treatment, may be useful in the treatment of many diseases with herbal methods today. Content analysis was used for the review and analysis of the selected study. The analysis and the meaning of the words were performed; the method and the quantity or dosage used is given in the pharmaceutical codex. The Latin names of the medicinal plants referred to in the book were determined. These analyses showed that this book, which is about making remedies from plants used for treatment, has a wide range of treatments for 72 different diseases. 59 different cures for these diseases are reported in the text. It has been observed that many of the treatments reported in the book are still used today. As a result, it is thought that this valuable work that has not been analyzed before will make a great contribution to the related field.